Safety in the administration of injectable medications: Scoping review (Research, Society and Development, 2021)
Objective: to raise scientific evidence on technologies for the safe administration of injectable drugs in hospitalized adult patients. Method: this is a study of the Scoping Review type, using the crossing of the descriptors Patient Safety, Medication Errors and Technology in the following databases: Medical Literature Analysis and Retrieval System Online Electronic Library Online, Science Direct, Virtual Health Library, Pubmed, Web of Science and Scopus. The choice of studies included in the sample and data extraction occurred in a paired manner by independent researchers. Results: 14 studies were classified as eligible. The interventions found were medication administration using a barcode, patient identification by plates, bracelets, radiofrequency and/or biometrics, personal digital assistants, mobile nursing carts, electronic medication administration record, safety syringe system based on key-lock adapters, smart infusion pumps, drugs organizer kits, storage bag, trays with dividers, adhesive in different colors for separating medicines by class, and double checking. Final considerations: The implementation of technologies, professionalism, changes in the organization and in the workplace linked to the empowerment of the patient and family/companion enables the quality of the injectable medication administration processes. It is considered an advantageous investment in technologies for the culture of safety.